Aberrant regulation of CXCR4 in cancer via deviant microRNA-targeted interactions. Issue 13 (9th December 2022) - Stuckel, Alexei J.; Khare, Tripti; Bissonnette, Marc; Khare, Sharad
ABSTRACT: CXCR4 is involved in many facets of cancer, including being a major player in establishing metastasis. This is in part due to the deregulation of CXCR4, which can be attributed to many genetic and epigenetic mechanisms, including aberrant microRNA–CXCR4 interaction. MicroRNAs (miRNAs) are a type of small non-coding RNA that primarily targets the 3' UTR of mRNA transcripts, which in turn suppresses mRNA and subsequent protein expression. In this review, we reported and characterized the many aberrant miRNA–CXCR4 interactions that occur throughout human cancers. In particular, we reported known target sequences located on the 3' UTR of CXCR4 transcripts that tumour suppressor miRNAs bind and therefore regulate expression by. From these aberrant interactions, we also documented affected downstream genes/pathways and whether a particular tumour suppressor miRNA was reported as a prognostic marker in its respected cancer type. In addition, a limited number of cancer-causing miRNAs coined 'oncomirs' were reported and described in relation to CXCR4 regulation. Moreover, the mechanisms underlying both tumour suppressor and oncomir deregulations concerning CXCR4 expression were also explored. Furthermore, the miR-146a-CXCR4 axis was delineated in oncoviral infected endothelial cells in the context of virus-causing cancers. Lastly, miRNA-driven therapies and CXCR4 antagonist drugs were discussed as potential future treatment options in reported cancers pertaining to deregulated miRNA–CXCR4 interactions.